Availability of Land, Water, Human and Technology Resources in the Development of Food Estate Areas in Merauke-Indonesia - Untari (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The development of a food estate area in Merauke requires the availability of adequate resources in terms of quality and quantity. The research objective is to analyze the availability of resources in the development of industrial estates based on agricultural production produced in the development of food estates . The research was conducted in the food estate development area, namely Merauke Regency, analyzing secondary data. The data were analyzed from spatial data and then analyzed using a qualitative descriptive analysis approach. Some observation indicators are data on the availability of agricultural land for cultivation, analysis of potential water sources and needs, availability of human resources, and supporting infrastructure. The results of the analysis show that the availability of Merauke’s land resources for the food estate is sufficient in terms of quantity and quality for agricultural cultivation, but has not been supported by adequate human resources, namely farmers and agricultural extension workers. Likewise with the availability of water resources and infrastructure facilities such as road networks, ports, electricity, and irrigation networks, it is necessary to revitalize existing facilities and add basic infrastructure networks for the development of a food estate area in Merauke.